THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE TO ENCOURAGE STUDENTS AT MARGOSARI KINDERGARTEN TO LEARN VOCABULARY - Riyanti, Anika; Rustipa, Katharina (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
Learning English vocabulary is a challenging subject for many students. Students were differ from adults in many ways, especially on the attention span of children is limited. They are entertaining and friendly and need further English language instruction. Additionally, they get more proficiency with their hands, ears, and eyes. To fully engage in learning in class, they require methods and surroundings that they can touch, hear, and see. Most kindergartens still think and struggle to comprehend the subject matter. They can typically understand language by responding to and obeying specific commands through regularly repeated phrases or sentences as if they had naturally learned their original language from their surroundings. The TPR approach, which has been shown to be effective in teaching vocabulary to young students, was investigated by the researcher. The researcher is interested in seeing young learners being taught vocabulary via TPR for this reason. This study is a qualitative descriptive investigation. Both the teacher and the students are the subject of this study. In order to collect data for this study, two different methods were used: observation and interview. The validity of the data which following the collection of data from the observed teaching-learning activity, the data were analyzed qualitatively to compare the results of observations with implementation according to theory, to evaluate students motivation based on the motivational characteristics obtained from the observations, and interpret them. The outcomes showed that the students were more motivated to learn vocabulary using the TPR approach. This can be achieved through the teacher's encouragement of students to learn vocabulary and the way the teacher teaches. In this case, students participate fully in class activities, thereby achieving the goal of implementing the total physical response approach.